The Inhibitor Endosidin 4 Targets SEC7 Domain-Type ARF GTPase Exchange Factors and Interferes with Subcellular Trafficking in Eukaryotes - Kania, Urszula; Nodzyński, Tomasz; Lu, Qing; Hicks, Glenn R; Nerinckx, Wim; Mishev, Kiril; Peurois, François; Cherfils, Jacqueline; De Rycke, Riet; Grones, Peter; Robert, Stéphanie; Russinova, Eugenia; et al. (The Plant cell, 2018)
The trafficking of subcellular cargos in eukaryotic cells crucially depends on vesicle budding, a process mediated by ARF-GEFs (ADP-ribosylation factor guanine nucleotide exchange factors). In plants, ARF-GEFs play essential roles in endocytosis, vacuolar trafficking, recycling, secretion, and polar trafficking. Moreover, they are important for plant development, mainly through controlling the polar subcellular localization of PIN-FORMED transporters of the plant hormone auxin. Here, using a chemical genetics screen in Arabidopsis thaliana, we identified Endosidin 4 (ES4), an inhibitor of eukaryotic ARF-GEFs. ES4 acts similarly to and synergistically with the established ARF-GEF inhibitor Brefeldin A and has broad effects on intracellular trafficking, including endocytosis, exocytosis, and vacuolar targeting. Additionally, Arabidopsis and yeast (Saccharomyces cerevisiae) mutants defective in ARF-GEF show altered sensitivity to ES4. ES4 interferes with the activation-based membrane association of the ARF1 GTPases, but not of their mutant variants that are activated independently of ARF-GEF activity. Biochemical approaches and docking simulations confirmed that ES4 specifically targets the SEC7 domain-containing ARF-GEFs. These observations collectively identify ES4 as a chemical tool enabling the study of ARF-GEF-mediated processes, including ARF-GEF-mediated plant development.
Keywords: proteiny huseníčku; Saccharomyces cerevisiae Proteins; Endocytosis; mutace; chromony; Arabidopsis; Saccharomyces cerevisiae; membránové transportní proteiny; membránové glykoproteiny; brefeldin A; Arabidopsis Proteins; DNA vazebné proteiny; Molecular Docking Simulation; Chromones; Guanine Nucleotide Exchange Factors; endocytóza; Membrane Transport Proteins; proteinové domény; simulace molekulového dockingu; Cell Membrane; Plants, Genetically Modified; Brefeldin A; Transcription Factors; transkripční faktory; Membrane Glycoproteins; buněčná membrána; výměnné faktory guaninnukleotidů; Saccharomyces cerevisiae - proteiny; Protein Transport; geneticky modifikované rostliny; Mutation; Protein Domains; DNA-Binding Proteins; transport proteinů